Konsep Pendidikan Islam dan Pemikiran Pendidikan Islam: Sebuah Literatur Review - Safitri, Lis; Nurlaela, Nurlaela; Wahyudin, Wahyudin; Asyik, Noor; Rohman, Abdul (Institute of Research and Public Service Universitas Jenderal Soedirman, 2023)
This research aims to find the concept of education in general and Islamic education based on the definitions expressed by scholars. This research is a literature review employing a scoping literature review approach. The results show that the definition of limited-broad education is a solution to the fragmentation of the definition of education in the broad term (throughout life) and education in the narrow term (classroom learning). Islamic education is based on Islamic principles in the Quran and Hadith or theories developed by scholars based on these principles. Scholars categorize Islamic educational thought based on different perspectives regarding its objectives, and educational thought can be categorized as humanism, perennials, essentialism, reconstructionism, and behaviorism. Regarding religious content, educational thought can be categorized as education in the wall, at the wall, and beyond the wall. Another categorization is religious-conservative (al-muhafizh), religious-rational (al-din al-'aqlani), and pragmatic-instrumental (al-dara`i).